2021
DOI: 10.7150/ijms.55421
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Pemphigoid and Diabetes medications: A disproportionality analysis based on the FDA Adverse Event Reporting System

Abstract: Background: The world's first Diabetes Medications (Insulin) was marketed in October 1923. Some studies suggested the association of diabetes medications with Bullous Pemphigoid (BP), especially the Dipeptidyl Peptidase 4 (DPP-4) inhibitors. The study aims to detect an association between diabetes medications (focusing on DPP-4 inhibitors) and bullous pemphigoid based on FDA Adverse Event Reporting System (FAERS). Methods: All spontaneous reports of diabetes medications inhibitors-related BP recorded in the FA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
(59 reference statements)
2
2
0
Order By: Relevance
“…Further, in the FAERS data, seven DPP4 inhibitors, i.e., vildagliptin, linagliptin, sitagliptin, alogliptin, teneligliptin, and saxagliptin, were identified, and we observed a significant association between the use of these compounds and BP incidence, independent of selectivity towards DPP8/9. These results are consistent with those of a previous study based on FAERS data, randomized controlled trials and Meta-analysis ( 39 , 44 , 45 ). These data may indicate that the inhibition of DPP4 enzyme activity increased the incidence of DPP4 inhibitor-induced BP.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further, in the FAERS data, seven DPP4 inhibitors, i.e., vildagliptin, linagliptin, sitagliptin, alogliptin, teneligliptin, and saxagliptin, were identified, and we observed a significant association between the use of these compounds and BP incidence, independent of selectivity towards DPP8/9. These results are consistent with those of a previous study based on FAERS data, randomized controlled trials and Meta-analysis ( 39 , 44 , 45 ). These data may indicate that the inhibition of DPP4 enzyme activity increased the incidence of DPP4 inhibitor-induced BP.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, in the present study, we used adverse event data from the FAERS database, on the basis of which several unexpected drug-drug interactions were identified as confounding factors ( 7 10 ). Our analysis in this regard not only suggested that DPP4 inhibitors could cause BP, as indicated by previous studies ( 39 , 40 ), but also indicated that lisinopril could suppress DPP4 inhibitor-induced BP. Conversely, the anti-PD1/PDL1 antibody group (nivolumab, pembrolizumab, cemiplimab, atezolizumab, avelumab, and durvalumab) showed increased risk of BP (ROR = 16, Z score = 48), and combination treatment with lisinopril did not affect their odds ratios (ROR=1.6, Z score = 1.2).…”
Section: Discussionsupporting
confidence: 82%
“…14 ROR and PRR were calculated per the methods mentioned in different pharmacovigilance retrospective studies. [15][16][17] A value of ROR-1.96SE >1 (SE-Standard Error) and PRR ≥2 were considered as the threshold value, above which it is regarded as a positive signal.…”
Section: Discussionmentioning
confidence: 99%
“…It aims to provide clean and curated access to the underlined reported adverse events and count reports stratified to an extraction condition 14 . ROR and PRR were calculated per the methods mentioned in different pharmacovigilance retrospective studies 15–17 . A value of ROR‐1.96SE >1 (SE‐ Standard Error) and PRR ≥2 were considered as the threshold value, above which it is regarded as a positive signal.…”
Section: Methodsmentioning
confidence: 99%